Penurunan Kadar Kekeruhan, BOD, dan COD Pada Limbah Laundry Menggunakan Biosorben Arang Eceng Gondok (Eichhornia crassipes) - Ngana, Mersi N.; Suwari, Suwari; Ola, Pius D. (Chemistry Notes, 2022)
Abstract Research has been carried out with the title of reducing turbidity, BOD, and COD levels in laundry waste using water hyacinth charcoal biosorbent which aims to determine the surface area of water hyacinth charcoal biosorbent on reducing turbidity, BOD, and COD in laundry waste using water hyacinth charcoal biosorbent, knowing the effect of water hyacinth charcoal biosorbent contact time on decreasing turbidity, BOD, and COD in laundry waste, and knowing the effect of water hyacinth charcoal biosorbent on decreasing turbidity, BOD, and COD in laundry waste. The adsorbent used was water hyacinth (Eichhornia crassipes). Water hyacinth adsorbents is a plant used as a cleaning agent in waters polluted by heavy metals, reducing the movement of organic waste so asto to facilitate sedimention. The water hyacinth charcoal adsorbent functions as an adsorbent, where the adsorbents functions to control wastewater pollution. The adsorption used was water hyacinth (Eichhornia crassipes). Water hyacinth adsorbents in reducing turbidity, BOD, and COD are surface area, time variation and adsorbents mass. Final results the highest level of water hyacinth adsorbent surface area of 44.0754 m2 /g occurred at a contact time of 60 minutes. The final results of water hyacinth adsorbent contact time between laundry waste, the hihghest decrease in turbidity level of 47.52 % occurred in 30 minutes, the highest decrease in BOD contect of 80.04 % occurred in contact time of 60 minutes, and the highest decrease in COD was 38.70 % occurred at a contact time of 120 minutes. The final results of the water hyacinth adsorbent mass between laundry wastes, the highest decrease in turbidity content of 47.27 % occurred in 3 gram mass, the highest decrease in BOD contect was 80.04 % occurred in 6 gram mass, and the highest decrease in COD content was 37.02 % occurs at a mass of 12 gram.